The allure of luxury brands' social media activities: a uses and gratifications perspective. Issue 3 (3rd June 2019) - Athwal, Navdeep; Istanbulluoglu, Doga; McCormack, Sophie Elizabeth
Abstract : Purpose: The purpose of this paper is to explore the social media marketing activities of luxury brands, guided by uses and gratifications theory (UGT). It examines the gratifications sought by millennials, a new core luxury consumer group, and the gratifications obtained when following and connecting with luxury brands. Design/methodology/approach: Online data are gathered from Facebook, Instagram and Twitter accounts of five top luxury brands. In addition, 30 in-depth interviews with millennials, the new generation of luxury consumers, were conducted. Thematic analysis strategy was followed to analyze the data and present the findings. Findings: Luxury brands remain distant and aloof, which helps them to maintain a sense of exclusivity. User activity, ranging from observations to commenting on and liking luxury brand content, leads to the gratification of two types of need: affective and cognitive. Two affective needs that are satisfied by luxury brands' social media marketing activities are aesthetic appreciation and entertainment. Cognitive needs are satisfied through the functional use of social media as an information source. Originality/value: Several studies have investigated social media from the perspective of UGT, but this study is the first to investigate the implications of luxury brands' social media usage with the lenses of UGT.